Adalimumab Accounts for Long-Term Control of Noninfectious Uveitis Also in the Absence of Concomitant DMARD Treatment: A Multicenter Retrospective Study - Alice Bitossi; Alessandra Bettiol; Elena Silvestri; Gerardo Di Scala; Daniela Bacherini; Giuseppe Lopalco; Vincenzo Venerito; Florenzo Iannone; Antonio Vitale; Gian Marco Tosi; Domenico Prisco; Stanislao Rizzo; et al. (Mediators of Inflammation)
Objective. This study was aimed at assessing the long-term ocular control of adalimumab (ADA) in a large real-world population with noninfectious primary or secondary uveitis, focusing on the steroid-sparing effect and on disease-modifying antirheumatic drug (DMARD) cotreatment. Methods. In this retrospective, multicenter study, the efficacy of ADA was evaluated in terms of ocular control, changes in best-corrected visual acuity (BCVA), corticosteroid-sparing effect, and drug retention rate, overall and stratified according to DMARD cotreatment. Results. 106 patients were included. 88.7% had an associated systemic disease. After 6 and 12 months, proportions of patients with effective ocular control were 83.7% and 83.3%, respectively. At last the follow-up, 94.6% of patients had satisfactory ocular control. No difference in terms of ocular control at all time points emerged among patients starting ADA for ocular vs. systemic involvements. Patients with poor baseline BCVA remained stable or improved, while those with good BCVA hardly worsened. At 6 and 12 months, the median dose of prednisone significantly reduced to 5 mg/day (0-5) and 2.5 mg/day (0-5) (p<0.001). Over a median follow-up of 36 months, 38 subjects discontinued ADA treatment. Mild to moderate side effects were reported in 7 patients (6.6%). ADA ocular control, corticosteroid-sparing effect, and drug retention rate were not influenced by the concomitant use of DMARDs. Conclusion. The long-term ocular control of ADA in noninfectious primary or secondary uveitis is confirmed, also for BCVA preservation. Concomitant use of DMARDs does not provide additional benefits to ADA alone in terms of ocular control, steroid spare, and drug retention rate.